Utwory osierocone jako zagadnienie prawa i kultury - Jarmuszkiewicz, Anna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The article presents contemporary definitions of orphan works, the problems associated with these definitions and the importance of the existence of orphan works for contemporary culture in the context of cultural memory.
Orphan works as the subject of law and culture
Keywords: copyright; orphan works; cultural memory; prawo autorskie; utwory osierocone; pamięć kulturowa